REFINING APPROACHES FOR THE OPTIMAL USE OF HUMAN POTENTIAL IN SMALL BUSINESS ENTERPRISES - Dustova Aziza Kakhramonovna (Modern American Journals, 2025)
This article focuses on the importance of effectively utilizing human resources in company management, highlighting global practices and theoretical approaches to improving employee performance and development. In particular, it emphasizes the strategies developed by the Japanese management school, which have proven to significantly enhance the effectiveness of human resource utilization in companies. The article discusses how linking a company's strategic goals with the personal development of its employees is a key factor for success.
Keywords: Human resource utilization, company management, employee development, strategic goals, japanese management school, professional training, skill development, technological advancements, economic effectiveness, social effectiveness, employee motivation, management practices